CHEMOSTRATIGRAPHY AND EVALUATION OF HYDROCARBON POTENTIAL OF THE BELATA BLACK SHALES, PERAK, PENINSULAR MALAYSIA - OWUSU BOATENG, ESTHER (2019)
Paleozoic black shales in Peninsular Malaysia forms 25% of its sedimentary area cover, however, research on the thermal maturity of the black shales and their economic potential have been overlooked. Hence, this research is aiming at establishing the deposition and stratigraphic zones of the Carboniferous black shales of the Belata Formation and to discuss their shale gas potential. Extensive fieldwork, petrographic, inorganic, and organic geochemical analyses were carried out on outcrop samples. X-ray diffraction, Energy-dispersive X-ray scanning electron microscopy, X-ray fluorescence, total organic carbon (TOC), Rock-Eval pyrolysis, and vitrinite reflectance measurements were conducted in this study.